THE ROLE OF CULINARY SECTOR MSME DEVELOPMENT ON COMMUNITY WELFARE IN SAMPANG CITY: PERAN PERKEMBANGAN UMKM SEKTOR KULINER TERHADAP KESEJAHTERAAN MASYARAKAT DI KOTA SAMPANG - Laily Nur Aini; Septian Eko Haryansyah; Zulviar Anas (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2025)
The development of MSMEs in the culinary sector is a strategic step that plays a significant role in improving the welfare of the people in Sampang City. This research was conducted using an interactive qualitative approach. While the selection of informants was carried out using a purposeful sampling technique. Based on the results of the study, it shows that the development strategy that can be implemented by culinary MSMEs is the MSME Development Strategy for the culinary sector through product innovation, collaboration and partnerships, and customer experience. Through this strategy, the role of MSME development on welfare can be seen from increased income, labor absorption, improved quality of life, sending children to higher education, economic stability, and self-development. This strategy is important so that culinary MSME actors can survive and thrive in the long term, so that it can be implemented and improve the welfare of the people in Sampang City.